2022
DOI: 10.1097/rlu.0000000000004467
|View full text |Cite
|
Sign up to set email alerts
|

Increased 18F-FAPI PET/CT Uptake in a Case of Brucellosis of Lumbar Vertebral Body

Abstract: Vertebral brucellosis is a relatively rare disease that usually emerges in animal husbandry areas. We report a case that brucellosis of lumbar vertebral body showed an intense uptake of FAPI on 18 F-FAPI PET/CT, which mimics to malignant lesions or vertebral tuberculosis. It is an interesting finding to realize that vertebral brucellosis is also one of the reasons for intense uptake of FAPI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…The patient’s symptoms of dysphagia gradually disappeared after balloon dilatation and 1-week oral rabeprazole. Multiple studies have confirmed that FAP can be expressed in a variety of infectious lesions, including Streptococcus infection, 1 COVID-19 infection, 2,3 organizing pneumonia, 4 syphilis infection, 5 tuberculosis infection, 6,7 pulmonary cryptococcus, 8 Brucella infection 9 . This case suggested that FAPI uptake can also be demonstrated in candidiasis.…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…The patient’s symptoms of dysphagia gradually disappeared after balloon dilatation and 1-week oral rabeprazole. Multiple studies have confirmed that FAP can be expressed in a variety of infectious lesions, including Streptococcus infection, 1 COVID-19 infection, 2,3 organizing pneumonia, 4 syphilis infection, 5 tuberculosis infection, 6,7 pulmonary cryptococcus, 8 Brucella infection 9 . This case suggested that FAPI uptake can also be demonstrated in candidiasis.…”
mentioning
confidence: 56%
“…Multiple studies have confirmed that FAP can be expressed in a variety of infectious lesions, including Streptococcus infection, 1 COVID-19 infection, 2,3 organizing pneumonia, 4 syphilis infection, 5 tuberculosis infection, 6,7 pulmonary cryptococcus, 8 Brucella infection. 9 This case suggested that FAPI uptake can also be demonstrated in candidiasis. Therefore, when we found lesions with increased FAPI uptake, we could not ignore its role as an inflammatory or infection imaging agent.…”
mentioning
confidence: 88%
“…We speculate that the high accumulation of 68 Ga-FAPI-04 in AVM stems from the uptake by the activated fibroblasts. Meanwhile, an increasing number of case studies have reported 68 Ga-FAPI-04 uptake in various nonmalignant etiologies, including myocardial infarction, 6 IgG4-related disease, 7,8 atherosclerotic plaque, 9 xanthogranulomatous cholecystitis, 10 tuberculosis, 11 osteoarthritis, 12 ankylosing spondylitis, 13 and brucellosis 14 . This case indicates that AVM should be considered as one of the differential diagnoses for abnormal 68 Ga-FAPI-04 uptake in the liver.…”
mentioning
confidence: 87%
“…However, FAP was also shown to be expressed in many types of nonmalignant bone or joint pathologies including arthritis, 13 fracture, 14 benign bone cyst, 15 fibrous dysplasia, 16 myositis ossificans, 17 avascular necrosis of the bone, 18 Schmorl node, 19 ankylosing spondylitis, 20 bone tuberculosis, 21 and other types of bone infection. 22 Thus, we speculate that sites of SAPHO involvement might be imaged with 68 Ga-DOTA-FAPI-04. The aim of this study is to evaluate the performance of 68 Ga-DOTA-FAPI-04 PET/CT in SAPHO and to compare it with the performance of 18 F-FDG PET/CT.…”
mentioning
confidence: 89%
“…Recently, 68 Ga-DOTA-FAPI-04, which targets fibroblast activation protein (FAP), is introduced in tumor imaging. However, FAP was also shown to be expressed in many types of nonmalignant bone or joint pathologies including arthritis, 13 fracture, 14 benign bone cyst, 15 fibrous dysplasia, 16 myositis ossificans, 17 avascular necrosis of the bone, 18 Schmorl node, 19 ankylosing spondylitis, 20 bone tuberculosis, 21 and other types of bone infection 22 . Thus, we speculate that sites of SAPHO involvement might be imaged with 68 Ga-DOTA-FAPI-04.…”
mentioning
confidence: 95%